Psychometric Properties of the Persian Version of the Teasing Questionnaire 23 - Ebrahimi, Ali; Elhami Athar, Mojtaba; Hakim Shooshtari, Mitra; Karsazi, Hossain; Storch, Eric A (Frontiers in Psychology, 2021)
The current study aimed to investigate the factor structure and internal consistency of the Persian version of the Teasing Questionnaire-Revised (TQ-R). Forward and backward translations of the TQ-R were performed; content and face validities were determined based on student samples as well as specialists’ comments. This study used cluster sampling and included 290 participants. The factor structure was assessed by confirmatory and exploratory factor analysis, and Cronbach's alpha coefficient was used to evaluate internal consistency. The result of the confirmatory factor analysis (CFA) did not confirm the five original factors. Exploratory factor analysis (EFA) revealed four factors and 23 items, explaining 52.03% of the total variance. The internal consistency of the Persian version of Teasing Questionnaire 23 was α = .92. The findings indicated that the Persian version of the TQ-R has sound psychometric properties and can be used as a valid and reliable tool in research and clinical outcomes.